Behavioural contributors to agricultural technology adoption: A toolkit for researchers and practitioners - Thai, Giang T. (2023)
In low-income countries, agriculture is the main source of livelihood for 59 percent of the population (World Bank 2019). Uncertainty is inherent in agriculture. Farming entails many elements that lie outside of farmers’ control such as (increasingly) weather and pest shocks (Chavas and Nauges 2019; Rosenzweig and Udry 2020; Moscona and Sastry 2021), price fluctuations (Bellemare et al. 2013), the quality of agricultural technologies (Bold et al. 2017; Ashour et al. 2019; Hoel et al. 2022), and other factors. Reducing poverty, improving food security, and charting a path for households out of poverty will require improvements in agricultural productivity (Bridle et al. 2019).